Integration Of Peace Communication And Conflict Resolution In Education System: The Case Of Myanmar - Hsu Thiri Zaw (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Education is always the foundation for the development in every country as it is essential for individual sectors such as politics, economics, social and cultural regardless of time and situation. Moreover, education can provide people knowledge, competencies, skills and attitudes that people powerfully engage in the development schemes of their societies. When figuring about education in the society is necessary for the public, peace communication and conflict resolution have been a key role for the diverse cultural communities with multicultural norms and practices to establish effective and sustainable development in education system. Promoting the education about peace and conflict resolution in the system can encourage the peace and stability of the communities and even to the students in their daily lives. The study focuses on integrating peace communication and conflict resolution in the education system and discusses about the direct and indirect approaches to the peace communication and conflict resolution education integration in Myanmar using case study research method presenting descriptive contexts, international examples and background information for in-depth analysis of various perspectives.